Multidisciplinary Management of Liver Metastases in Colorectal Cancer : Early Diagnosis and Treatment - Qin, Xinyu; Xu, Jianmin; Zhong, Yunshi (Springer Netherlands : Imprint: Springer, 2017)
This book focuses on early diagnosis and multidisciplinary treatment, which is the key to preventing the occurrence of the liver metastases in colorectal cancer, and to increasing the resection rate of the liver metastasis foci and the 5-year survival after surgery. This book is divided into five parts: the introduction, basics, diagnosis, treatment and prevention. It has 20 chapters in total, covering the latest advances in colorectal cancer liver metastases epidemiology, pathogenesis, molecular diagnostics, marker screening, imaging technology, surgery, chemotherapy and prevention, etc. It provides professionals with up-to-date and comprehensive information on colorectal liver metastases. This book is relevant for senior surgeons and physicians working in oncology, general surgery, chemotherapy, digestive medicine, liver medicine and hepatic surgery. Editors Xinyu Qin and Jianmin Xu are Professors at the Department of General Surgery, Zhongshan Hospital, Fudan University, Shanghai, China. Editor Yunshi Zhong is an Associate Professor at the same department.